Challenges in Sustainable Degradability of Bio-Based and Oxo-Degradable Packaging Materials during Anaerobic Thermophilic Treatment - Magdalena Zaborowska; Katarzyna Bernat; Bartosz Pszczółkowski; Irena Wojnowska-Baryła; Dorota Kulikowska (Energies, 2021)
Although the manufacturers labelled commercially available bio-based products as biodegradable, there are discrepancies concerning the time frame for their sustainable biodegradation and methane production. Starch-based, polylactic acid-based and oxo-degradable foils were anaerobically treated in thermophilic condition (55 °C, 100 days). The effect of alkaline pretreatment on foils degradation was also investigated. To examine changes in their mechanical and physical properties, static tensile tests and microscopic analyses, FTIR and surface roughness analyses were conducted. Despite the thermophilic condition, and the longer retention time compared to that needed for biowaste, a small amount of methane was produced with bio-based foils, even after pretreatment (ca. 30 vs. 50 L/kg VS) and foils only lost functional and mechanical properties. The pieces of bio-based materials had only disintegrated, which means that digestate may become contaminated with fragments of these materials. Thus, providing guidelines for bio-based foil treatment remains a challenge in waste management.